Community Empowerment Based on Religious Groups “JSN Cengkir Gading” - Khoirul Rahman; Kevin Kurnia Gumilang (Prospect Publishing, 2023)
Most religious groups only focus on religious activities and do not touch on other aspects of life. JSN Cengkir Gading in addition to carrying out the function of the